(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research dealt with the dimensions of marketing strategies as an independent variable with its four sub-dimensions (pricing, distribution channel management, marketing communications, market planning) and customer prosperity as a dependent variable, A sample of managers working in the Ministry of Commerce was selected. The research relied on the opinions of (136) managers. The problem of the research was diagnosed through the field coexistence conducted by the researcher in the ministry, which lies in the weakness of marketing strategies, so the dimensions of marketing strategies were proposed in addressing the weakness of the customer’s prosperity, due to the department managers’ lack of sufficient knowledge of the dimensions of marketing strategies on the one hand and its close relationship to the prosperity of the customer on the other hand. The research sought to achieve a set of goals, the most important of which are: clarifying and presenting the concepts related to marketing strategies and customer prosperity in the Ministry of Commerc , and standing on the basic dimensions that make up the concept of marketing strategies and customer prosperity in the Ministry of Commerce, with a focus on the most important dimensions. The research relied on the analytical descriptive approach, and to achieve these goals the researcher used the questionnaire in the practical aspect of the research, as well as the research and studies that are related to the topic of research in the theoretical aspect with reliance on the (SPSS) program in testing and analyzing the impact hypotheses and the relationship between the research variables. The research reached a set of conclusions by testing and analyzing the hypotheses adopted by the research, and the research concluded with a set of recommendations that, if adopted, could contribute to activating the dimensions of marketing strategies.